Application of Model Based Learning in Mathematics for Elementary School Students - Latifah, Kusnul (Universitas Sebelas Maret, 2022)
This article as a literature review aims to find out the importance of applying the Problem Based Learning model in the process of learning mathematics. Teaching and learning activities so far still use the conventional model, where the teacher dominates the learning process in the classroom. Thus, students only receive the information conveyed by the teacher. As a result, in the learning process students tend to be passive. This is due to the lack of understanding of students in mathematics. Therefore, the process of learning mathematics in elementary schools needs active interaction between teachers and students. The teacher does not dominate when learning, it takes active involvement of students in the learning process. Based on this, to be able to create an active learning process, teachers need to increase creativity in learning, one of which is by holding variations in teaching so that an active and fun learning process is created so that students can be motivated in learning by using the Problem Based Learning model in learning mathematics in elementary schools that can stimulate students' curiosity in learning.